Peer assessment of student-produced mechanics lab report videos - Douglas, Scott S. (Phys Rev Lett, 2017)
We examine changes in students’ rating behavior during a semester-long sequence of peer evaluation laboratory exercises in an introductory mechanics course. We perform a quantitative analysis of the ratings given by students to peers’ physics lab reports, and conduct interviews with students. We find that peers persistently assign higher ratings to lab reports than do experts, that peers begin the semester by giving high ratings most frequently and end the semester with frequent middle ratings, and that peers go through the semester without much change in the frequency of low ratings. We then use student interviews to develop a model for student engagement with peer assessment. This model is based on two competing influences which appear to shape peer evaluation behavior: a strong disinclination to give poor ratings with a complementary preference to give high ratings when in doubt, and an attempt to develop an expertlike criticality when assessing peers’ work.